Islamic Communiation Strategy of Public Relations of Solok District in Disseminating Regional Development Iformation - Ardi, Supri; Arif, Ernita; Azwar, Azwar (Hikmah, 2024)
This research aims to analyze the Islamic communication strategy implemented by the public relations department of Solok Regency. Emphasizing the social construction of reality through the social constructivism paradigm, this research focuses on understanding how these strategies are formulated. This research uses qualitative research methods with descriptive methods, examining public communication management and the dissemination of development information. The analysis uses descriptive qualitative methods, including the stages of data reduction, presentation, and conclusion drawing. The results revealed that it is important to understand local social and cultural dynamics in formulating effective communication strategies. The research reveals the importance of a broader stakeholder engagement approach to managing public and development communication in Solok District, which may include involving the general public, non-governmental organizations and the private sector. By encouraging such collaboration, this research argues that the effectiveness of public communication and community participation in development efforts can be significantly enhanced. This contribution highlights the need for inclusive communication strategies for successful development initiatives.